Modeling and simulation of the aqueous humor flow in the human eye - Dörsam, Simon; Olkhovskiy, Vladislav; Friedmann, Elfriede (Proceedings in applied mathematics and mechanics, 2019)
A mathematical model for the physiology of the aqueous humor flow in the human eye is developed. The governing equations are the Stokes and Darcy equations with certain physical characteristic parame...
Gesehen am 18.01.2021